Prilagajanje odmerjanja protimikrobnih zdravil pri kritično bolnih - Cvikl Knehtl, Maja (Farmacevtski vestnik, 2022)
Dosing of antimicrobial drugs in critically ill patients remains challenging. Choosing an appropriate antimicrobial drug with effectiveness against the most likely pathogen, as well as the selection of an appropriate dosing regimen that will provide therapeutic concentration at the site of infection, is essential. When choosing a dosing regimen we should consider the phamacokinetic properties of the selected antimicrobial agents (hydrophilicity and lipophilicity, pharmacokinetic/pharmacodinamic index), the patient’s individual parameters (body weight, effect of critically illness on pharmacokinetics, kidney function – acute kidney failure, augmented renal clearance or possible application of different dialysis techniques, and extracorporeal membrane oxygenation) and susceptibility of the causative pathogen. This review article summarises factors to be considered in adjusting the dosing regimen of antimicrobial drugs in critically ill patients.
Keywords: antibiotics; Antibiotiki; antimicrobial drugs; critically ill patients; dializne metode; dialysis techniques; farmakokinetično/farmakodinamični indeks; kritično bolni; ledvična funkcija; pharmacokinetic/pharmacodynamic index; protimikrobna zdravila; renal clearance